PEMENUHAN ATAS PERUMAHAN SALAH SATU UPAYA PENANGGULANGAN KEMISKINAN - Diasana Putra, I Dewa Gede Agung; Gde Yana, Anak Agung (Jurnal Natah, 2007)
The efforts to tackle poor people problems are through basic right fulfilment like food, health, education,work, water, sanitation and housing. Housing is one of fulfilment which difficult to get by poor people inIndonesia. About 4,5 millions backlog unit of housing, also improving of slump area that are the problemsof housing in Indonesia.The objective of this study is to know the fulfilment strategy of housing and settlement for poor people, tocarrying out of Nation Strategy of tackling poverty especially housing. In Order to achieve this objective,this research uses literature studies method from any reference.Building material engineering is one method to obtain the cheap houses with safety, comfort and healthaspect, whether standardization construction system and modular coordination’s system.